Chapter Diritto del lavoro e valori - Del Punta, Riccardo (Studi e saggi, 2022)
The author argues that the topic of values is strictly inherent to the labour law discourse. Law must not only be provided, but also justified, and this calls values into question. However, discussing values from the viewpoint of philosophy or law is profoundly different, as the legal discussion must consider what law is, in the historical context of its development. The author then wonders if the classical values of labour law are still adequate, or if - as it is argued - they need to be revisited, for both conceptual and historical reasons, in order to promote the worker's subjectivity. The problem of the relationship between labour law's values and economic instances is finally addressed, arguing in favour of a dialogue between the two disciplines.